Sub-federal ecological modernization: a case study of Colorado's new energy economy - Giannakouros, Stratis, author; Stevis, Dimitris, advisor; Davis, Sandra, committee member; Carolan, Michael, committee member (Colorado State University. Libraries, 2013)
European nations have often employed policies of explicit government intervention as a preferred means of addressing environmental and economic challenges. These policies have ranged from grey industrial policies focused solely on industrial growth, competitiveness and innovation to policies of stronger ecological modernization, which seek to align industrial interests with environmental protection. In recent years these policies have been mobilized to address the threat of climate change and promote environmental innovation. While some US Administrations have similarly recognized the need to address these challenges, the particular historical and political institutional dynamics of the US have meant that explicit government intervention has been eschewed in favor of more indirect strategies when dealing with economic and environmental challenges. This is evident in the rise of sub-federal policies at the level of US states. Supported by federal laboratories and public research, US states have adopted policies that look very much like sub-federal versions of industrial or ecological modernization policy. This thesis uses the Colorado case to highlight the importance of sub-federal institutions in addressing environmental and economic challenges in the US and explore its similarities to, and differences from, European approaches. To achieve this goal it first develops an analytical scheme within which to place policy initiatives on a continuum from grey industrial policy to strong ecological modernization policy by identifying key institutions that are influential in each policy type. This analytical scheme is then applied to the transitional renewable energy policy period from 2004-2012 in the state of Colorado. This period starts with the adoption of a renewable energy portfolio in 2004 and includes the 'new energy economy' period from 2007-2010 as well as the years since. Looking at three key turning points this paper interprets the 'new energy economy' strategy using the analytical scheme developed and identifies the political and social institutions that frame this transition. Drawing upon these findings, the paper analyses the implications of the Colorado case for understanding sub-federal initiatives in the US and concludes with a summary of the broader comparative institutional lessons.
Keywords: ecological modernization; renewable energy; innovation; green industrial policy